(untitled) (The Research of Medical Science Review, 2025)
Objectives: To determine the frequency of myths and misconceptions regarding the use of long-acting reversible contraception among women in AJK, Pakistan. Study design: Cross sectional study. Place and Duration of the study: Abbas Institute of Medical Sciences (AIMS), Muzaffarabad from September 2024 to March 2025. Methodology: A total of 343 women seeking maternal & child health services and family planning services were included. They were interviewed in detail to determine different myths and misconceptions regarding the use of long-acting reversible contraception. Data was analyzed using SPSS version 22. Results: In this study, 343 patients were included. Median age was 29.00 (41.00 – 18.00) years. Median age at marriage was 21.00 (33.00 – 16.00) years. Median age at the birth of the first child 22.00 (33.00 – 17.00) years. Frequency of myths and misconceptions regarding the use of long-acting reversible contraception was 165 (48.10%). Amongst these patients (n = 165), most common myth & misconception regarding LARC use was that it is very difficult to get pregnant after stopping using contraceptives that was found in 39 (23.64%) patients followed by perception that their use causes infertility found in 34 (20.60%) women, displeasure of God found in 28 (16.97%) women and perception that their use adversely affect women’s health found in 28 (16.97%) women. Conclusion: Myths and misconceptions regarding the use of long-acting reversible contraception among women in AJK, Pakistan is too high reported at 48.10%.